Targeted photosensitizer delivery: A prospective approach to vitiligo photochemotherapy - S. R. Utz; G. B. Sukhorukov; V. V. Tuchin; D. A. Gorin; E. A. Genina; Yu. I. Svenskaya; E. E. Talnikova (Vestnik Dermatologii i Venerologii, 2019)
Aim. In this work, the authors set out to develop an effective method for the intrafollicular delivery of “Ammi majus fructuum furocumarines” photosensitizer (AMFF) followed by UVA irradiation (λ = 320–400 nm). Materials and methods. The proposed delivery method consists in using calcium carbonate particles acting as AMFF carriers. In vivo monitoring of hair follicle filling was carried out via optical coherence tomography, as well as by means of analyzing epilated hair using confocal laser scanning microscopy. Following the administration of free and encapsulated AMFF to three healthy volunteers, the character of UVA-induced skin pigmentation was registered under dermatoscopic examination. Results. The obtained results demonstrate a profuse filling of hair follicles with calcium carbonate particles, thus confirming the possibility of intrafollicular photosensitizer delivery. It was established that exposure to UVA irradiation causes intense pigment accumulation in the area of AMFF carrier administration. Conclusion. The proposed method of the targeted photosensitizer delivery allows photochemical therapy to be improved.